ANALYSIS OF KINETICS OF CAST IRON ALLOYING THROUGH SLAG PHASE - O. S. Komarov; V. I. Volosatikov; I. B. Provorova; T. D. Komarova (Литьë и металлургия)
The mechanism of cast iron alloying through slag phase due to use of nickel and copper oxides is considered and the analysis of kinetics regularity of alloying in case of absence of fuse in the form of milled cast-iron chips in slag and at their presence in it is carried out.